2010
DOI: 10.1002/pros.21270
|View full text |Cite
|
Sign up to set email alerts
|

miR‐125b promotes growth of prostate cancer xenograft tumor through targeting pro‐apoptotic genes

Abstract: BACKGROUND Increasing evidence demonstrates that aberrantly-regulated microRNAs (miRNAs) contribute to the initiation and progression of human cancer. We previously have demonstrated that miR-125b stimulated the growth of prostate cancer (CaP) cells. In this study, we further determined the influence of miR-125b on the pathogenesis of prostate cancer. METHODS To evaluate the effect of miR-125b on xenograft tumor growth, male athymic mice were subcutaneously injected with PC-346C-miR-125b cells that stably ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
148
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(161 citation statements)
references
References 45 publications
8
148
0
Order By: Relevance
“…22 The upregulation of miR-125b was shown to be associated with the reduction of BCL2-antagonist/killer (BAK1), P53 and PUMA levels, all of which are known targets of miR-125b. 22,23 This is further supported by the fact that lowering miR-125b expression by androgen withdrawal was associated with an increase in BAK1, P53 and PUMA expression. 23 …”
mentioning
confidence: 75%
See 2 more Smart Citations
“…22 The upregulation of miR-125b was shown to be associated with the reduction of BCL2-antagonist/killer (BAK1), P53 and PUMA levels, all of which are known targets of miR-125b. 22,23 This is further supported by the fact that lowering miR-125b expression by androgen withdrawal was associated with an increase in BAK1, P53 and PUMA expression. 23 …”
mentioning
confidence: 75%
“…22,23 This is further supported by the fact that lowering miR-125b expression by androgen withdrawal was associated with an increase in BAK1, P53 and PUMA expression. 23 …”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The expression of miR-125b is also found in mouse preimplantation embryos although its exact role has not been eluciated [16]. Several proteins, including p53, have been reported to be the targets of miR-125b and mediate its action in various physiological and pathological events, including neuronal differentiation [12,17,18], immune response [19,20] and cancer [10,[21][22][23]. Particularly, p53 has been reported to mediate the effect of miR-125b on embryo development [15].…”
Section: Hcomentioning
confidence: 99%
“…In order to create a comprehensive list of miRNAs dysregulated in PCa, we combined data from our recently published miRNA microarray comparing PCa with normal matched prostate tissue from the same patient (Schaefer et al , 2010a ) and did a literature search for additional reported miRNAs dysregulated in PCa when compared to normal prostate tissue (Sylvestre et al , 2007 ;Ambs et al , 2008 ;Shi et al , 2011 ;Sun et al , 2011 ).…”
Section: Mirna Dysregulation In Pcamentioning
confidence: 99%